Winner of the SLS Annual Conference Best Paper Prize 2016: Knowledge and landscape in wind energy planning*. (2nd January 2018) - Lee, Maria
Abstract : 'Landscape' is relatively underexplored in legal scholarship, notwithstanding its occasional centrality to legal analysis, and the ways in which law contributes to the shaping of landscape. Wind energy is an especially rich area for the exploration of landscape; not only do wind farms consistently raise concerns about landscape, but the existence of climate change complicates the response to local concern. Most of the legal literature on 'knowledge' focuses on the ways in which different 'expert' knowledges find their way into, and then shape, legal processes and decisions. This article is more concerned with the ways in which the planning system receives different knowledge claims, and validates some of them. The discussion turns around four tentative categories of knowledge claim: expert or technical knowledge claims; lay (or sometimes local) knowledge claims; prior institutional knowledge claims; and professional planning knowledge claims. Knowledge of the complex, dynamic and plural idea of landscape in any particular case is constructed in the process of decision making and reason giving through a careful layering of these different sorts of knowledge claim.